(untitled) - Joko Santoso, Nina Yulianti, Masliani, Sulmin Gumiri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Forest and land fires that occurred in Central Kalimantan Province were disasters on a national scale which occurred on a small and large scale every year. The population of Central Kalimantan consists of various ethnicities, religions and cultures, one of which is the Buddhist community. The purpose of this research is to measure the level of understanding and attitudes of Buddhists towards forest and land fires in Central Kalimantan, to analyze the relationship between Buddhist understanding, attitudes and roles of forest and land fires in Central Kalimantan, and to formulate the efforts that can be made by Buddhists in prevent and control forest and land fires in Central Kalimantan. The method used is data collection from respondents using a purposive questionnaire in three research areas, namely Palangka Raya City, East Kotwaringin Regency and West Kotawaringin Regency using a Likert Scale, according to Sugiyono (2010: 93) Likert scale is used to measure attitudes, opinions and perceptions. a person or group of people about social phenomena. For each answer option given a score, the respondent must describe, support the statement. The result found in this study is that there is a significant correlation between age and Buddhist understanding and attitudes towards forest and land fires. The understanding of Buddhists in West Kotawaringin District is very uniform, but they tend to have different attitudes about the forest and land fire cases. In contrast, the understanding of Buddhists in East Kotawaringin District tends to vary, but they tend to have the same attitude towards forest and land fires. Meanwhile, in Palangka Raya City, the level of Buddhist understanding of forest and land fires is consistent with their attitude.